CSIG-42. HIGH THROUGHPUT KINOME AND TRANSCRIPTOME ANALYSES REVEAL NOVEL THERAPEUTIC TARGETS IN NF2-DEFICIENT MENINGIOMA. (5th November 2018) - Beauchamp, Roberta; Erdin, Serkan; Angus, Steven; Stuhlmiller, Timothy; Oblinger, Janet; Jordan, Justin; Haggarty, Stephen J; R. Plotkin, Scott; Chang, Long-Sheng; L. Johnson, Gary; F. Gusella, James; Ramesh, Vijaya
Abstract: Meningiomas (MN), the most common adult primary intracranial tumor, arise from the arachnoid/meninges and are non-responsive to chemotherapies with a high recurrence rate despite surgery, necessitating effective non-invasive therapies. Our previous work showed that NF2 loss activates mechanistic target of rapamycin complex 1 (mTORC1) and mTORC2 signaling, which led to past NF2 clinical trials using rapalogs (RAD001/everolimus), and current meningioma clinical trials with dual mTORC1/mTORC2 inhibitor (mTORi) AZD2014. To understand additional dysregulated, potentially druggable pathways, we undertook an 'omics approach of large-scale kinomics and RNA-sequencing employing CRISPR-modified human arachnoidal cells (ACs), NF2 -expressing vs NF2 -null. In NF2 -null ACs, several kinases were elevated including erythropoietin-producing hepatocellular (EPH)-receptor tyrosine kinase (RTK) family members, Src family kinase (SFK) members, and c-KIT, all targets of dasatinib. In vitro treatment of MN cells using mTORi (AZD2014 or INK128) and dasatinib enhanced growth inhibition upon combination mTORi+dasatinib. In vivo treatment of an orthotopic mouse MN model showed moderate response to dasatinib with stronger response using INK128 or INK128+dasatinib (e-published in Neuro-Oncology). Our transcriptomic data also revealed increased expression of several ligands/growth factors, particularly NRG1/neuregulin. Expanding these results, we have confirmed increased expression of NRG1 in human NF2 -null ACs. We also find NF2 -null ACs secrete NRG1, and in conditioned-media experiments we observe stimulation of ErbB3, EPHA2 and mTOR pathways, suggesting an autocrine signaling mechanism. NF2 -null AC or MN cells, when stimulated with exogenous NRG1, show enhanced activation of mTOR and EPH pathways besides ErbB3 signaling. Further, lapatinib (multi-ErbB inhibitor) but not erlotinib (EGFR inhibitor) attenuates the NRG1-stimulated activation of ErbB3, EPHA2 and mTOR, suggesting that NRG1-induced activation is EGFR-independent. Taken together, our results support a mechanistic link where NF2 loss increases NRG1/ErbB signaling to EPH/SFK and mTOR pathways, which may be a critical driver of tumorigenesis, thus providing a therapeutic opportunity to co-target these pathways in NF2 -deficient meningiomas.